Public Private Partnership and Prospects of ICT in Sustainable Development of Rural India - AMIRULLAH (International Journal of Research in Social Science, 2014)
The sustainable development of rural India is one of the most important challenges at present. The greatest obstacles for its development is long distances from cities and inadequate infrastructure for education, health services, power, agricultural markets, poor quality roads and other services. 21 st century is called the age of Information and Communication Technology (ICT) that has played a significant role in developing the communication channels in rural areas, especially in education, local agricultural information and clinical services, health and social protection, grievance submission, community discussions, and so forth. It is also associated with economic benefits such as higher productivity, lower costs, new economic opportunities, job creation, innovation, and increased trade. Many ICT projects are running like Akshaya in Kerala, Saksham by Microsoft, Gyandoot in Madhya Pradesh, e-Mitra in Rajasthan, etc. It has helped in rural development in a sustainable way but has given rise to digital divide as it has penetrated limited rural areas due to budgetary constraint, lack of technical knowledge, in addition to high rural populations, more than 22 languages and scores of dialects, lack of adequate infrastructures, failures of power systems and poor broadband networks. Public Private Partnership (PPP) has emerged as a key strategy for infrastructure improvement, more effective service delivery and fiscal efficiency. It has helped in creation of IT infrastructure, mobile phone production, software development, hardware manufacturing facilities, the rollout of optical fibre cables, business process outsourcing, application development and so on. It will make digital villages through e-health, e- learning, Citizens’ service delivery, e-commerce, information access (and sharing), e-taxation, e- participation, the use of ICT by people with disabilities or e-rural development. Many PPP projects are under various stages of implementation and provide vast opportunities for Indian states in sustainable development of rural areas.